PEMBIASAAN PERILAKU RELIGIUS MENGGUNAKAN PENDEKATAN BEHAVIORISTIK PADA SISWA MADASAH IBTIDAIYAH - giyarmi; Katni, Katni; Dina, Nadia Filosofi; Ridloi, Muhammad Aldin (LPPM STAI Muhammadiyah Probolinggo, 2025)
The purpose of this study is to analyze the habituation of religious behavior using a behaviorist approach on students of MI Nurul Islam Wonogiri, as well as to analyze its impact. This research approach is qualitative, the type of research is Field Research, the researcher as a key instrument that collects research data through observation, in-depth interviews, and documentation also analyzes the data. The results are: 1) the habituation of religious behavior is a continuous repetition over a long period of time with the aim of improving religious behavior. The habituation includes: a) the ritual dimension (sharia); b) the ideological dimension (aqidah); c) the intellectual dimension (science); d) the dimension of experience or appreciation (experiential); e) the consequential dimension (practice). The relationship with the five religious dimensions, MI Nurul Islam teachers gradually accustom students to activities; 2) the impact of the habituation of religious behavior on students from the stimulus that has been done by both parents and teachers has an impact on increasing very good responses. Proven by students becoming accustomed to applying the five religious dimensions. 3) When students are given stimulus by providing good examples in the form of thoughts, actions and words, providing guidance, direction, approaching and working together with parents, which is done consistently in every dimension of religious habituation, then the students' response becomes accustomed to and loves the five religious dimensions to be applied in everyday life.